A retrospective study on the acceptability, feasibility, and effectiveness of LoveYourBrain Yoga for people with traumatic brain injury and caregivers. Issue 12 (5th June 2021) - Donnelly, Kyla Z.; Baker, Kim; Pierce, Ramsay; St. Ivany, Amanda R.; Barr, Paul J.; Bruce, Martha L.
Abstract: Purpose: To conduct a mixed methods, pre-post, retrospective study on the feasibility, acceptability, and effectiveness of the LoveYourBrain Yoga program. Materials and Methods: People were eligible if they were a traumatic brain injury survivor or caregiver, age 15–70, ambulatory, and capable of gentle exercise and group discussion. We analyzed attendance, satisfaction, and mean differences in scores on Quality of Life After Brain Injury Overall scale (QOLIBRI-OS) and four TBI-QOL/Neuro-QOL scales. Content analysis explored perceptions of benefits and areas of improvement. Results: 1563 people (82.0%) participated ≥1 class in 156 programs across 18 states and 3 Canadian provinces. Mean satisfaction was 9.3 out of 10 ( SD 1.0). Mixed effects linear regression found significant improvements in QOLIBRI-OS ( B 9.70, 95% CI: 8.51, 10.90), Resilience ( B 1.30, 95% CI: 0.60, 2.06), Positive Affect and Well-being ( B 1.49, 95% CI: 1.14, 1.84), and Cognition ( B 1.48, 95% CI: 0.78, 2.18) among traumatic brain injury survivors ( n  = 705). No improvement was found in Emotional and Behavioral Dysregulation, however, content analysis revealed better ability to regulate anxiety, anger, stress, and impulsivity. Caregivers perceived improvements in physical and psychological health. Conclusions: LoveYourBrain Yoga is feasible and acceptable and may be an effective mode of community-based rehabilitation. IMPLICATIONS FOR REHABILITATION: People with traumatic brain injury and their caregivers often experience poor quality of life and difficulty accessing community-based rehabilitation services. Yoga is a holistic, mind-body therapy with many benefits to quality of life, yet is largely inaccessible to people affected by traumatic brain injury in community settings. Participants in LoveYourBrain Yoga, a six-session, community-based yoga with psychoeducation program in 18 states and 3 Canadian provinces, experienced significant improvements in quality of life, resilience, cognition, and positive affect. LoveYourBrain Yoga is feasible and acceptable when implemented on a large scale and may be an effective mode of, or adjunct to, community-based rehabilitation.